Effect of bout duration on exercise intensity and technical performance of small-sided games in soccer - Fanchini, M.; Azzalin, A.; Castagna, C.; Schena, F.; McCall, A.; Impellizzeri, F. M. (The Journal of Strength and Conditioning Research, 2011)
To examine whether the increase in bout duration would affect the exercise intensity and technical actions, we manipulated bout duration during a typical small-sided game drill (SSG) in male soccer players. Nineteen players (mean ± SD: age 24 ± 4 years, body mass 74 ± 4 kg, and height 180 ± 5 cm) completed three bouts of a 3-a-side drill at three different bout durations: 2, 4, and 6 minutes. Exercise intensity was quantified using heart rate (HR) and rating of perceived exertion (RPE). A nonsignificant duration × bout interaction was found for HR (p = 0.757). Heart rates of bout 1 were significantly lower than bout 2 (p = 0.004) and bout 3 (p = 0.049). The effect of duration was close to significance for HR (p = 0.057) with 6-minute SSG significantly lower than 4-minute SSG (p = 0.004). Duration × bout interaction did not reach the significance for RPE (p = 0.096). The RPE significantly increased along the bouts (p < 0.001) but was not affected by duration (p = 0.763). No effect of duration was found for number of technical actions per minute (p > 0.111). A significant effect of bout was only found for successful passes (p = 0.018). Partially confirming our hypothesis, the increase in bout duration from 2 to 6 minutes resulted in a decrease in intensity only between the 4- and 6-min SSG. However, duration did not influence the technical actions and proficiency. The magnitude of changes in HR (89.5 vs. 87.8 of maximum) is probably not enough to induce different training adaptations. Therefore, coaches can use different bout durations with minimal impact on exercise intensity and without compromising technical proficiency.